From Glamorous to Everyday Use: Kebaya as the Medium of Women's Self-Expression - Nita Trismaya; Yasmine Z. Shahab; Mia Siscawati (Wacana Journal of Social and Humanity Studies, 2022)
As a national costume of Indonesia, the Kebaya experienced a shift in its form, function, and meaning upon entering the post-reform period. This shift has impacted changing the 'classic' kebaya model, which follows the traditional pakem standard, to a 'modern' kebaya with more freedom in its design. One of the modern Kebaya styles is the 'party kebaya. ' Since the 'classic' Kebaya is considered impractical, outdated, and anti-fashion, the 'party kebaya' is more preferable to be worn for various occasions such as weddings, parties, graduations, and the like. However, unfortunately, the 'party kebaya' design tends to ignore the pakem standard, so sometimes the outfit can no longer be considered the traditional 'kebaya'. In observing this phenomenon, women from kebaya associations concerned about preserving the tradition of wearing the Kebaya have introduced the 'Back to kebaya' movement to express their concern. The model of the Kebaya that they chose is the 'classic' Kebaya that could be worn for daily activities, not the fancy 'party kebaya.' This raises the question: why do these women care about preserving the tradition of wearing the Kebaya, and how do they gain attention and raise awareness from the public? This qualitative research applied the ethnographic method involving women members of various kebaya associations in Jakarta as research subjects and observing them in their activities and social media. This research was analyzed with the concept of self-expression, which is the author's interpretation of the theory of dress identity. This paper is aimed to present the novelty of the tradition of the Kebaya from an anthropology perspective, as well as understanding it from the perspective of the women who wear the Kebaya. Keywords: classic, kebaya, party, self-expression, women